A dynamic hydrogen bond composite resin carbon nanotube conductive paste, a preparation method and application thereof
Patent Information
- Application Number
- CN202610938797.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-26
- Publication Date
- 2026-10-23
AI Technical Summary
更为具体的,本发明拟解决下述技术问题:1)碳纳米管在水性体系中易团聚、分散不均匀的问题;2)现有导电浆料成膜后极片柔韧性不足,高压实或高硅含量条件下易开裂、掉粉、断带的问题;3)长期循环过程中,因硅碳负极体积膨胀收缩导致导电网络断裂、界面阻抗增长、容量衰减的问题;4)现有导电浆料难以兼顾导电性、分散性、粘结性和循环稳定性的综合性能要求
(1)显著提高碳纳米管在水性体系中的分散稳定性:通过界面锚定单体的分步引入和复合树脂的原位包覆,碳纳米管在水性介质中实现了均匀、稳定的分散。实验数据表明,本发明导电浆料在25℃密封储存6个月后,粘度变化率控制在16.7%~20.5%,远优于对比例的60.6%~67.9%,且未出现分层、沉降或凝胶现象。
Smart Images

Figure CN122968288A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to a composite conductive paste for the negative electrode of lithium-ion batteries, and more particularly to a conductive paste containing dynamically hydrogen-bonded polyurethane-acrylate composite resin carbon nanotubes, its preparation method and application. Background Technology
[0002] Lithium-ion batteries are the core power source for new energy vehicles, energy storage systems, and consumer electronics products, and their energy density, rate performance, and cycle life have always been the focus of industry attention. With the widespread application of silicon-carbon anode materials and high-pressure solid graphite anodes, higher requirements have been placed on anode sheets to withstand processing and cycle stability.
[0003] In the negative electrode, the conductive paste plays a crucial role in establishing electron transport channels. The continuity of the conductive network, its dispersion stability, and its interfacial compatibility with the active material and current collector all affect rate discharge, cycle retention, and the mechanical integrity of the electrode.
[0004] Carbon nanotubes (CNTs) are widely used as conductive agents in lithium-ion battery anodes due to their excellent aspect ratio, high conductivity, and mechanical reinforcement. However, CNTs exhibit poor dispersibility in aqueous systems, easily leading to entanglement and aggregation, resulting in discontinuous conductive networks and increased electrode resistance. Furthermore, when used in conjunction with silicon-carbon anodes, the volume expansion of silicon during charging and discharging can cause the conductive network to break, resulting in increased interfacial impedance and capacity decay.
[0005] To improve the dispersibility of carbon nanotubes, various methods have been explored in existing technologies. For example, surface coating or modification of carbon nanotubes with polymers can enhance their dispersion stability in aqueous systems. One patent discloses a technique for coating single-walled carbon nanotubes with polymethyl methacrylate (PMMA), but this coating layer is a single polymer with limited functionality, and the coated carbon nanotubes still suffer from conductive network degradation during long-term cycling. Another technique uses hydroxylated carbon nanotubes combined with linear acrylate-acrylonitrile copolymers, which, while suppressing the volume expansion of silicon-based materials to some extent, suffers from a simple polymer structure and lacks adaptive design for electrode flexibility and conductive network.
[0006] Furthermore, the resin component in existing conductive slurries is typically used only as a dispersant or simple binder, making it difficult to simultaneously ensure the dispersion stability of carbon nanotubes, the flexibility of the electrode film after formation, and the retention of the conductive network during cycling. Especially under conditions of high silicon content or high compaction density, the electrode is prone to brittle cracking, powder shedding during bending, and strip breakage during rolling, which seriously affects the battery's processing performance and cycle life.
[0007] Therefore, developing a novel conductive paste that can simultaneously improve the dispersion stability of carbon nanotubes, electrode flexibility, interfacial adhesion, and the ability to maintain the conductive network during cycling is of great practical significance and application value. Summary of the Invention
[0008] This invention aims to overcome the technical defects of existing carbon nanotube conductive pastes in lithium-ion battery anode applications, and provides a composite conductive paste and its preparation method that can simultaneously improve the dispersion stability of carbon nanotubes, electrode flexibility, interfacial adhesion, and conductive network retention during cycling. More specifically, this invention aims to solve the following technical problems: 1) the problem of carbon nanotubes easily agglomerating and unevenly dispersing in aqueous systems; 2) the problem of insufficient electrode flexibility after existing conductive pastes are formed, and the problem of easy cracking, powder shedding, and band breakage under high compaction or high silicon content conditions; 3) the problem of conductive network breakage, interfacial impedance increase, and capacity decay caused by the volume expansion and contraction of silicon-carbon anodes during long-term cycling; 4) the difficulty of existing conductive pastes in meeting the comprehensive performance requirements of conductivity, dispersibility, adhesion, and cycling stability.
[0009] To achieve the above-mentioned objectives, the present invention employs the following technical solution.
[0010] This invention first provides a dynamic hydrogen-bonded composite resin carbon nanotube conductive paste, which, based on 100% of the total mass of the conductive paste, mainly consists of the following components by mass percentage: Multi-walled carbon nanotubes: 1.0%–6.0%; Conductive carbon black 0.1%–3.0%; Polyurethane-acrylate composite resin 5.0%~20.0%; Interface anchoring monomers: 0.05%–3.0%; Dispersant 0.1%–5.0%; pH adjuster 0.01%~1.0%; The remainder is an aqueous medium.
[0011] The polyurethane-acrylate composite resin is formed by chemical bonding of polyurethane segments and acrylate polymer components, and the polyurethane segments contain dynamic reversible hydrogen bond structures.
[0012] The polyurethane segments possess a flexible main chain structure, endowing the conductive slurry with excellent flexibility and elasticity after film formation, effectively alleviating the mechanical stress generated by the volume expansion and contraction of the silicon-carbon anode during charging and discharging. Simultaneously, the dynamic reversible hydrogen bonds in the polyurethane segments, such as the UPy quadruple hydrogen bonds, can reversibly break under stress to dissipate energy and reform after stress relief, thereby maintaining the integrity of the conductive network and suppressing the increase in interfacial impedance during cycling. The acrylate polymer component has strong polarity and good compatibility with carbon materials, enhancing the interfacial bonding between the composite resin and carbon nanotubes, conductive carbon black, and anode active materials, promoting the uniform construction of the conductive network. Furthermore, the polyurethane segments and acrylate polymer component form a synergistic effect: the polyurethane segments provide flexibility and stress buffering, while the acrylate component provides interfacial compatibility and dispersion stability. The composite resin formed by their chemical bonding possesses comprehensive properties that cannot be achieved by a single component.
[0013] The interface anchoring monomer has carbon nanotube adsorption groups and polymerizable reactive groups. The carbon nanotube adsorption groups include pyrene, catechol, dopamine, and phosphate esters, while the polymerizable reactive groups include methacrylate groups. The interface anchoring monomer of this invention is introduced in two steps, as detailed below.
[0014] The first part of the interface anchoring monomer is covalently bonded to the acrylate polymer component: during in-situ emulsion polymerization, this part of the interface anchoring monomer copolymerizes with the acrylate monomer, "pre-setting" the anchoring groups on the composite resin molecular chain. When the composite resin coats the surface of carbon nanotubes or comes into contact with the negative electrode active material, these anchoring groups can form strong interactions with the surface of carbon nanotubes or active materials, such as π-π stacking, coordination, or hydrogen bonding, significantly enhancing the interfacial bonding strength between the conductive paste and the electrode material.
[0015] The second part involves the adsorption of interfacial anchoring monomers onto the surface of the multi-walled carbon nanotubes. Added during the pre-dispersion stage, these monomers directly adsorb onto the surface of the carbon nanotubes, effectively preventing aggregation and improving their dispersion stability in aqueous systems through steric hindrance and electrostatic repulsion. Simultaneously, the interfacial anchoring monomers adsorbed on the carbon nanotube surface retain polymerizable reactive groups. When subsequently mixed with the composite resin, they can copolymerize with the acrylate components in the resin or form chemical crosslinks, thereby "anchoring" the carbon nanotubes to the composite resin network and constructing a continuous interfacial bond from resin to carbon nanotubes.
[0016] The two parts of the interface anchoring monomers introduced in stages exert their specific functions through synergistic effects: the two parts of anchoring monomers act on the composite resin phase and the carbon nanotube phase respectively, forming a "bridging structure" through chemical bonds or strong physical interactions, so that the conductive network remains highly stable during electrode rolling and cyclic charging and discharging, effectively suppressing the breakage of the conductive network and the increase of interface impedance caused by volume expansion.
[0017] The conductive paste of this invention employs a composite of multi-walled carbon nanotubes and conductive carbon black. Multi-walled carbon nanotubes, with their high aspect ratio, can establish long-range conductive pathways between the negative electrode active material particles, while avoiding the dispersion difficulties and excessively high paste viscosity problems associated with excessively long carbon nanotubes. Conductive carbon black fills the gaps between the carbon nanotube network and the active material particles, forming short-range conductive bridges. Together, they construct a continuous and efficient three-dimensional conductive network, significantly reducing electrode resistance and improving rate performance.
[0018] Preferably, the dynamic reversible hydrogen bond structure is selected from one or more of the following: urea-based hydrogen bond structure, bisurea-based hydrogen bond structure, and 2-urea-4[1H]-pyrimidinone (UPy) quadruple hydrogen bond structure. Introducing a dynamic reversible hydrogen bond structure can provide reversible physical crosslinking during the cyclic expansion and contraction of the negative electrode material, thereby enhancing the stress dissipation and structural recovery capabilities of the polymer network.
[0019] Preferably, the interface anchoring monomer is selected from one or more of pyrene methacrylate, catechol acrylate, dopamine methacrylamide, and phosphate methacrylate. The pyrene structure can form π-π interactions with the carbon nanotube surface, the catechol or dopamine structure can enhance adhesion to the carbon material and anode material surface, and the phosphate ester structure helps improve the bonding stability with silicon-carbon materials or electrode interfaces.
[0020] Preferably, the multi-walled carbon nanotubes have a diameter of 5–30 nm, a length of 5–15 μm, and a specific surface area of 100–350 m² / g.
[0021] Preferably, the polyurethane-acrylate composite resin has an average particle size of 50–500 nm, wherein the acrylate polymer component accounts for 20%–70% of the total mass of the composite resin. Controlling the particle size and proportion of the composite resin can balance slurry stability, film formation continuity, and electrode interface adhesion performance. Preferably, the dispersant includes one or more of polyurethane dispersants, polycarboxylate dispersants, and lignin sulfonate dispersants. The pH adjuster includes one or more of triethanolamine, ammonia solution, and 2-amino-2-methyl-1-propanol.
[0022] Preferably, the conductive slurry has a pH of 7.5–10 and a solid content of 6%–15%. Controlling the pH and solid content helps maintain the dispersion stability of the aqueous slurry system and its compatibility with subsequent negative electrode active material slurries.
[0023] Preferably, the mass ratio of the multi-walled carbon nanotubes, polyurethane-acrylate composite resin and conductive carbon black, calculated by solid mass, is 1:2.0-3.3:0.1-0.5.
[0024] This invention also provides a method for preparing the aforementioned dynamic hydrogen-bonded composite resin carbon nanotube conductive paste, comprising the following steps: Step 1, preparing a polyurethane dispersion containing polymerizable unsaturated groups: Step 11: Under dry conditions, react the diol and diisocyanate at 60–80°C for 2–4 hours to form a polyurethane prepolymer. The diol is selected from polyether diols, polycarbonate diols, or polyester diols with a number average molecular weight of 500–5000, wherein the molar ratio of NCO:OH to diisocyanate is 1.2–2.0:1.
[0025] Step 12: Add a chain extender containing a dynamic reversible hydrogen bond structure to the polyurethane prepolymer, the amount added being 1% to 10% of the mass of the polyurethane prepolymer, and react at 50 to 70°C for 1 to 2 hours; then add a capping monomer containing vinyl unsaturated groups, the amount added being 5% to 15% of the mass of the polyurethane prepolymer, and react at 50 to 70°C for 1 to 2 hours to obtain the reaction product; add an aqueous medium for dispersion to obtain a polyurethane dispersion containing polymerizable unsaturated groups.
[0026] The chain extender containing a dynamic reversible hydrogen bond structure is selected from one or more of the following: a urea-containing hydrogen bond structure, a diurea-containing hydrogen bond structure, and a 2-urea-4[1H]-pyrimidinone (UPy) quadruple hydrogen bond structure; the end-capping monomer containing a vinyl unsaturated group is selected from one or more of the following: hydroxyethyl methacrylate and hydroxypropyl acrylate.
[0027] Step 2, Preparation of polyurethane-acrylate composite resin: Acrylate monomers, first part of the interface anchoring monomers and free radical initiators are added to the polyurethane dispersion obtained in step 1, and in-situ emulsion polymerization is carried out at 70-90℃ for 3-4 hours to form polyurethane-acrylate composite resin.
[0028] The acrylate monomer is selected from one or more of butyl acrylate, ethyl acrylate, methyl methacrylate, butyl methacrylate, hydroxyethyl acrylate, and hydroxyethyl methacrylate; the mass ratio of the acrylate monomer to the polyurethane solid component in the polyurethane dispersion is 0.3 to 1.5:1 based on solid mass conversion.
[0029] The first portion of the interface anchoring monomer accounts for 20% to 80% of the total interface anchoring monomer, and the interface anchoring monomer is selected from one or more of pyrene methacrylate, catechol acrylate, dopamine methacrylamide, and phosphate methacrylate.
[0030] The free radical initiator is selected from one or more of ammonium persulfate, potassium persulfate, azobisisobutyramidine hydrochloride, and persulfate / bisulfite redox initiation systems, and the amount added is 0.1% to 2.0% of the mass of the acrylate monomer.
[0031] Step 3, Preparation of multi-walled carbon nanotube dispersion: Multi-walled carbon nanotubes, the second part of the interface anchoring monomer and the dispersant were added to deionized water. The mixture was first sheared at high speed of 4000-8000 rpm for 60-120 min, and then ultrasonically dispersed at 200-500 W for 10-30 min to obtain a multi-walled carbon nanotube dispersion.
[0032] Wherein, the second part of the interface anchoring monomer is the remaining part of the total amount of the interface anchoring monomer excluding the first part of the interface anchoring monomer; the mass ratio of the multi-walled carbon nanotubes to the dispersant is 1:0.2 to 0.8; and the solid content of the multi-walled carbon nanotube dispersion is 10% to 20%.
[0033] Step 4, Prepare the conductive paste: The multi-walled carbon nanotube dispersion obtained in step 3 is mixed with the polyurethane-acrylate composite resin obtained in step 2, and then conductive carbon black and pH adjuster are added and stirred evenly to obtain the dynamic hydrogen bond composite resin carbon nanotube conductive slurry.
[0034] Based on solid mass conversion, the mass ratio of multi-walled carbon nanotubes, polyurethane-acrylate composite resin, and conductive carbon black is 1:2.0~3.3:0.1~0.5.
[0035] The present invention also provides the application of the aforementioned dynamic hydrogen-bonded composite resin carbon nanotube conductive slurry in the preparation of lithium-ion battery negative electrode sheets.
[0036] Specifically, the conductive slurry is mixed with a negative electrode active material, a binder, a thickener, and an aqueous medium, and then stirred, dispersed, coated, dried, and rolled to obtain the lithium-ion battery negative electrode sheet. Preferably, the negative electrode active material includes silicon-carbon material, graphite, or a mixture of both.
[0037] The negative electrode prepared using the conductive paste of this invention maintains good crack resistance under high compaction density due to the flexibility provided by the polyurethane segments in the composite resin and the stress dissipation effect of dynamic reversible hydrogen bonds. The "bridging structure" formed by the stepwise introduction of interface anchoring monomers ensures uniform dispersion of carbon nanotubes in the aqueous system, significantly improving the electrode's peel strength. Furthermore, the conductive network remains stable and the interfacial impedance increases slowly during cycling. The synergistic conductive network of multi-walled carbon nanotubes and conductive carbon black reduces electrode resistance and improves rate performance.
[0038] Compared with the prior art, the present invention has the following beneficial effects: (1) Significantly improves the dispersion stability of carbon nanotubes in aqueous systems: Through the stepwise introduction of interface-anchored monomers and in-situ coating with composite resin, carbon nanotubes achieve uniform and stable dispersion in aqueous media. Experimental data show that after being sealed and stored at 25°C for 6 months, the viscosity change rate of the conductive paste of the present invention is controlled at 16.7% to 20.5%, which is far better than the 60.6% to 67.9% of the comparative example, and no stratification, sedimentation or gelation phenomenon is observed.
[0039] (2) The flexibility and crack resistance of the electrode sheet are significantly improved: The dynamic reversible hydrogen bonds in the polyurethane chain segments endow the composite resin with excellent stress dissipation ability. Combined with the elasticity of the polyurethane itself, the negative electrode sheet maintains good flexibility even under high compaction density (1.45~1.70g / cm³). After repeated bending tests (bending a 5mm diameter round rod 20 times), the electrode sheet coating remained intact without peeling, while the comparison sample showed obvious cracks and powdering. This characteristic effectively reduces the risk of R-corner material loss and roll breakage rate during electrode sheet processing and hot pressing of the core.
[0040] (3) Reduced electrode resistance and improved rate performance: The composite conductive network of multi-walled carbon nanotubes and conductive carbon black, combined with the stable coating of conductive components by composite resin, significantly reduces electrode resistance. Data from the examples show that the film resistance after electrode rolling is 1.81–1.94 mΩ, lower than the 1.98–2.05 mΩ of the comparative example; the capacity retention rate of the lithium-ion battery at 3C rate reaches 93.9%–95.2%, significantly better than the 88.5%–89.5% of the comparative example.
[0041] (4) Significantly extended cycle life and suppressed interfacial impedance growth: Dynamic reversible hydrogen bonds play a reversible physical cross-linking role during the volume expansion / contraction of the silicon-carbon anode, continuously repairing the conductive network and maintaining interfacial stability. After 800 cycles, the capacity retention rate of the battery of the present invention reached 94.2%–95.8%, far higher than the 82.6%–85.1% of the comparative example; the interfacial impedance growth rate was only 21.6%–30.4%, while the comparative example was as high as 50.0%–57.2%. This indicates that the conductive paste of the present invention can effectively slow down the degradation of the conductive network and the deterioration of the interface during long-term cycling.
[0042] (5) Improved electrode peel strength and processing stability: The strong interfacial bonding between the composite resin and carbon nanotubes, as well as the good compatibility between the resin and the negative electrode active material, significantly improves the electrode peel strength. The peel strength after rolling reaches 17.8–22.8 mN / mm, which is higher than the 13.8–14.2 mN / mm of the comparative example. At the same time, the negative electrode slurry remains uniform after standing for 48 hours, without stratification or hard sedimentation, indicating that the conductive slurry of the present invention has good compatibility with conventional negative electrode systems such as CMC and SBR.
[0043] In summary, this invention solves multiple technical challenges, such as carbon nanotube dispersion, electrode flexibility, conductive network cycle retention, and processing stability, through a synergistic technical solution involving dynamically reversible hydrogen bond-modified polyurethane-acrylate composite resin, stepwise introduction of interface anchoring monomers, and carbon nanotube / carbon black composite conductive network. Attached Figure Description
[0044] Figure 1 This is a 200nm electron microscope image of the carbon nanotube conductive paste prepared in Example 1 of the present invention.
[0045] Figure 2 This is a 200nm electron microscope image of the carbon nanotube conductive paste prepared in Example 2 of the present invention.
[0046] Figure 3 This is a 200nm electron microscope image of the carbon nanotube conductive paste prepared in Example 3 of the present invention.
[0047] Figure 4 This is a 200nm electron microscope image of the carbon nanotube conductive paste prepared in Example 4 of the present invention.
[0048] Figure 5 This is a 200nm electron microscope image of the carbon nanotube conductive paste prepared in Example 5 of the present invention.
[0049] Figure 6 This is a 200nm electron microscope image of the carbon nanotube conductive paste prepared in Example 6 of the present invention.
[0050] Figure 7 This is a 500nm electron microscope image of the carbon nanotube conductive paste prepared in Comparative Example 1 of this invention.
[0051] Figure 8 This is a 500nm electron microscope image of the carbon nanotube conductive paste prepared in Comparative Example 2 of this invention.
[0052] Figure 9 This is a 500nm electron microscope image of the carbon nanotube conductive paste prepared in Comparative Example 3 of the present invention. Detailed Implementation
[0053] The technical solution will be further explained below with reference to specific embodiments. Example 1
[0054] In this embodiment, a carbon nanotube conductive paste with dynamic reversible hydrogen bond composite resin was prepared. The specific preparation process is as follows.
[0055] (1) Under dry nitrogen protection, polycarbonate diol with a number average molecular weight of 2000 was added to the reaction vessel and dehydrated under vacuum at 80°C for 1 h. After cooling to 70°C, isophorone diisocyanate was added so that the molar ratio of isocyanate to diol was 1.6:1 (NCO:OH). The reaction was carried out at 70°C for 3 h to obtain polyurethane prepolymer.
[0056] (2) Bis(hydroxyethyl)urea was added to the polyurethane prepolymer obtained in step (1) as a chain extender containing dynamic reversible hydrogen bond units, and the amount added was 5% of the mass of the polyurethane prepolymer. After reacting at 60°C for 1 h, hydroxyethyl methacrylate was added as a capping monomer with a vinyl unsaturated structure, and the amount added was 10% of the mass of the polyurethane prepolymer. Then, the reaction was carried out at 60°C for 1 h. After the reaction was completed, deionized water was added and dispersed to obtain a polyurethane dispersion containing polymerizable unsaturated groups.
[0057] (3) An acrylate monomer composition consisting of methyl methacrylate, butyl acrylate, and hydroxyethyl acrylate is added to the polyurethane dispersion obtained in step (2), along with dopamine methacrylamide and ammonium persulfate initiator accounting for 50% of the total amount of interfacial anchoring monomers. In-situ emulsion polymerization is carried out at 80°C for 3 hours to obtain a polyurethane-acrylate composite resin. In this scheme, the mass ratio of acrylate monomers to polyurethane solid components in the polyurethane dispersion is 0.8:1 based on solid mass; the amount of ammonium persulfate added is 0.8% of the mass of acrylate monomers. The obtained polyurethane-acrylate composite resin, tested by a dynamic light scattering particle size analyzer, has an average particle size of approximately 180 nm, and the acrylate polymer component accounts for approximately 44% of the total mass of the composite resin.
[0058] (4) Multi-walled carbon nanotubes, the remaining 50% of dopamine methacrylamide, and polycarboxylate dispersant were added to deionized water. The mixture was first sheared at 6000 rpm for 70 min, and then ultrasonically dispersed at 300 W for 20 min to obtain a multi-walled carbon nanotube dispersion. In this scheme, the diameter of the multi-walled carbon nanotubes was 10-20 nm, the length was 5-15 μm, and the specific surface area was about 200 m² / g; the mass ratio of multi-walled carbon nanotubes to dispersant was 1:0.4, and the solid content of the resulting dispersion was 15%.
[0059] (5) Mix the multi-walled carbon nanotube dispersion obtained in step (4) with the polyurethane-acrylate composite resin obtained in step (3), then add conductive carbon black and triethanolamine, and stir until homogeneous to obtain a conductive slurry. Based on 100% of the total mass of the conductive slurry, where all components except the aqueous medium are based on the mass of effective solids or effective ingredients, the formed conductive slurry includes: Multi-walled carbon nanotubes 3.0%; Conductive carbon black 0.8%; Polyurethane-acrylate composite resin: 8.4%; Interface anchoring unit 0.6%; Dispersant 1.2%; Triethanolamine 0.2%; The remainder is deionized water.
[0060] The resulting conductive slurry had a pH of 8.5 and a solid content of 14.2%. Based on solid mass conversion, the mass ratio of multi-walled carbon nanotubes, polyurethane-acrylate composite resin, and conductive carbon black was 1:2.8:0.27. Example 2
[0061] In this embodiment, a carbon nanotube conductive paste containing a dynamically reversible hydrogen-bonded composite resin was prepared. The specific preparation process is as follows.
[0062] (1) Under the condition that the system is kept dry, polyether diol with a number average molecular weight of 3000 is added to the reaction vessel, and vacuum dehydrated at 80°C for 1 h. After cooling to 65°C, hexamethylene diisocyanate is added so that the molar ratio of isocyanate to diol is 1.4:1 (NCO:OH). The reaction is carried out at 65°C for 3 h to obtain polyurethane prepolymer.
[0063] (2) A 2-ureido-4[1H]-pyrimidinone derivative was added to the polyurethane prepolymer obtained in step (1) as a chain extender containing dynamic reversible hydrogen bond units. The amount added was 3% of the mass of the polyurethane prepolymer. After reacting at 55°C for 1.5 h, hydroxypropyl acrylate was added as a capping monomer with a vinyl unsaturated structure. The amount added was 8% of the mass of the polyurethane prepolymer, and the reaction was continued for another 1 h. After the reaction was completed, deionized water was added and the mixture was dispersed to obtain a polyurethane dispersion containing polymerizable unsaturated groups.
[0064] (3) An acrylate monomer composition consisting of ethyl acrylate, methyl methacrylate, and hydroxyethyl methacrylate is added to the polyurethane dispersion obtained in step (2), along with pyrene methacrylate and azobisisobutyramidine hydrochloride initiator accounting for 40% of the total amount of interfacial anchoring monomers. In-situ emulsion polymerization is carried out at 75°C for 4 hours to obtain a polyurethane-acrylate composite resin. In this scheme, the mass ratio of acrylate monomers to polyurethane solid components in the polyurethane dispersion is 0.5:1 based on solid mass; the amount of initiator added is 0.5% of the mass of acrylate monomers. The obtained polyurethane-acrylate composite resin has an average particle size of approximately 220 nm, and the acrylate polymer component accounts for approximately 33% of the total mass of the composite resin.
[0065] (4) Multi-walled carbon nanotubes, the remaining 60% of pyrene methacrylate and polyurethane dispersant were added to deionized water. The mixture was first sheared at 4000 rpm for 120 min, and then ultrasonically dispersed at 250 W for 25 min to obtain a multi-walled carbon nanotube dispersion. In this scheme, the diameter of the multi-walled carbon nanotubes was 5-15 nm, the length was 5-10 μm, and the specific surface area was about 250 m² / g; the mass ratio of multi-walled carbon nanotubes to dispersant was 1:0.25, and the solid content of the resulting dispersion was 10%.
[0066] (5) Mix the multi-walled carbon nanotube dispersion obtained in step (4) with the polyurethane-acrylate composite resin obtained in step (3), then add conductive carbon black and ammonia solution, and stir until homogeneous to obtain a conductive slurry. Based on 100% of the total mass of the conductive slurry, where all components except the aqueous medium are based on the mass of effective solids or effective ingredients, the above conductive slurry includes: Multi-walled carbon nanotubes 1.6%; Conductive carbon black 0.3%; Polyurethane-acrylate composite resin 5.0%; Interface anchoring unit 0.15%; Dispersant 0.4%; The ammonia solution contains 0.05% of the active ingredient. The remainder is deionized water.
[0067] The resulting conductive slurry had a pH of 8.0 and a solid content of 7.5%. Based on solid mass conversion, the mass ratio of multi-walled carbon nanotubes, polyurethane-acrylate composite resin, and conductive carbon black was 1:3.13:0.19. Example 3
[0068] In this embodiment, a carbon nanotube conductive paste with dynamic reversible hydrogen bond composite resin was prepared. The specific preparation process is as follows.
[0069] (1) Under the condition that the system is kept dry, polyester diol with a number average molecular weight of 1500 is added to the reaction vessel, and vacuum dehydrated at 80°C for 1 h. After cooling to 75°C, toluene diisocyanate is added so that the molar ratio of isocyanate to diol is 1.8:1 (NCO:OH). The reaction is carried out at 75°C for 2.5 h to obtain polyurethane prepolymer.
[0070] (2) A mixture of bis(hydroxyethyl)urea and 2-ureido-4[1H]-pyrimidinone derivatives was added to the polyurethane prepolymer obtained in step (1) as a chain extender containing dynamic reversible hydrogen bond units, with a total addition amount of 8% of the mass of the polyurethane prepolymer. After reacting at 65°C for 1 h, a mixture of hydroxyethyl methacrylate and hydroxypropyl acrylate was added as a capping monomer with a vinyl unsaturated structure, with a total addition amount of 12% of the mass of the polyurethane prepolymer, and the reaction was continued for another 1 h. After the reaction was completed, deionized water was added and dispersed to obtain a polyurethane dispersion containing polymerizable unsaturated groups.
[0071] (3) An acrylate monomer composition consisting of butyl methacrylate, butyl acrylate, and hydroxyethyl methacrylate is added to the polyurethane dispersion obtained in step (2), along with a mixture of phosphate methacrylate and catechol acrylate accounting for 60% of the total amount of interfacial anchoring monomers, and potassium persulfate initiator. In-situ emulsion polymerization is then carried out at 85°C for 3 hours to obtain a polyurethane-acrylate composite resin. In this scheme, based on solid mass conversion, the mass ratio of acrylate monomers to the polyurethane solid component in the polyurethane dispersion is 1.2:1; the amount of initiator added is 1.2% of the mass of the acrylate monomers. The obtained polyurethane-acrylate composite resin has an average particle size of approximately 260 nm, and the acrylate polymer component accounts for approximately 55% of the total mass of the composite resin.
[0072] (4) Multi-walled carbon nanotubes, the remaining 40% of the mixture of phosphate methacrylate and catechol acrylate, and lignin sulfonate dispersant were added to deionized water. The mixture was first sheared at 8000 rpm for 60 min, and then ultrasonically dispersed at 400 W for 15 min to obtain a multi-walled carbon nanotube dispersion. In this scheme, the diameter of the multi-walled carbon nanotubes was 15-30 nm, the length was 8-15 μm, and the specific surface area was about 180 m² / g; the mass ratio of multi-walled carbon nanotubes to dispersant was 1:0.27, and the solid content of the resulting dispersion was 18%.
[0073] (5) Mix the multi-walled carbon nanotube dispersion obtained in step (4) with the polyurethane-acrylate composite resin obtained in step (3), then add conductive carbon black and 2-amino-2-methyl-1-propanol, and stir until homogeneous to obtain a conductive slurry. Based on 100% of the total mass of the conductive slurry, excluding the aqueous medium, all components are calculated by effective solids or effective ingredients. The conductive slurry includes: Multi-walled carbon nanotubes 3.0%; Conductive carbon black 1.0%; Polyurethane-acrylate composite resin 8.0%; Interface anchoring unit 0.5%; Dispersant 0.8%; 0.1% 2-Amino-2-methyl-1-propanol; The remainder is deionized water.
[0074] The resulting conductive slurry had a pH of 9.0 and a solid content of 13.4%. Based on solid mass conversion, the mass ratio of multi-walled carbon nanotubes, polyurethane-acrylate composite resin, and conductive carbon black was 1:2.67:0.33. Example 4
[0075] In this embodiment, a carbon nanotube conductive paste with dynamic reversible hydrogen bond composite resin was prepared. The specific preparation process is as follows.
[0076] (1) Under the condition that the system is kept dry, a mixture of polyether diol with a number average molecular weight of 1000 and polycarbonate diol with a number average molecular weight of 2000 is added to a reaction vessel and dehydrated under vacuum at 80°C for 1 h. After cooling to 70°C, a mixture of isophorone diisocyanate and hexamethylene diisocyanate is added so that the molar ratio of isocyanate to diol is 1.5:1 (NCO:OH). The reaction is carried out at 70°C for 3.5 h to obtain polyurethane prepolymer.
[0077] (2) Bis(hydroxyethyl)urea was added to the polyurethane prepolymer obtained in step (1) as a chain extender containing dynamic reversible hydrogen bond units, and the amount added was 4% of the mass of the polyurethane prepolymer. After reacting at 60°C for 1 h, hydroxyethyl methacrylate was added as a capping monomer with a vinyl unsaturated structure, and the amount added was 6% of the mass of the polyurethane prepolymer, and the reaction was continued for another 1.5 h. After the reaction was completed, deionized water was added and dispersed to obtain a polyurethane dispersion containing polymerizable unsaturated groups.
[0078] (3) An acrylate monomer composition consisting of ethyl acrylate and methyl methacrylate is added to the polyurethane dispersion obtained in step (2), along with pyrene methacrylate and a persulfate / bisulfite redox initiation system accounting for 30% of the total amount of interfacial anchoring monomers. In-situ emulsion polymerization is carried out at 70°C for 4 hours to obtain a polyurethane-acrylate composite resin. In this scheme, the mass ratio of acrylate monomers to polyurethane solid components in the polyurethane dispersion is 0.3:1 based on solid mass; the amount of initiator added is 0.3% of the mass of acrylate monomers. The obtained polyurethane-acrylate composite resin has an average particle size of about 150 nm, and the acrylate polymer component accounts for about 23% of the total mass of the composite resin.
[0079] (4) Multi-walled carbon nanotubes, the remaining 70% of pyrene methacrylate and polycarboxylate dispersant were added to deionized water. The mixture was first sheared at 5000 rpm for 80 min, and then ultrasonically dispersed at 200 W for 30 min to obtain a multi-walled carbon nanotube dispersion. In this scheme, the diameter of the multi-walled carbon nanotubes was 10-20 nm, the length was 5-12 μm, and the specific surface area was about 220 m² / g; the mass ratio of multi-walled carbon nanotubes to dispersant was 1:0.6, and the solid content of the resulting dispersion was 12%.
[0080] (5) Mix the multi-walled carbon nanotube dispersion obtained in step (4) with the polyurethane-acrylate composite resin obtained in step (3), then add conductive carbon black and triethanolamine, and stir until homogeneous to obtain a conductive slurry. Based on 100% of the total mass of the conductive slurry, where all components except the aqueous medium are based on the mass of effective solids or effective ingredients, the above conductive slurry includes: Multi-walled carbon nanotubes 2.0%; Conductive carbon black 0.2%; Polyurethane-acrylate composite resin 6.0%; Interface anchoring unit 0.3%; Dispersant 1.2%; Triethanolamine 0.1%; The remainder is deionized water.
[0081] The resulting conductive slurry had a pH of 8.3 and a solid content of 9.8%. Based on solid mass conversion, the mass ratio of multi-walled carbon nanotubes, polyurethane-acrylate composite resin, and conductive carbon black was 1:3.0:0.1. Example 5
[0082] In this embodiment, a carbon nanotube conductive paste with dynamic reversible hydrogen bond composite resin was prepared. The specific preparation process is as follows.
[0083] (1) Under the condition that the system is kept dry, polycarbonate diol with a number average molecular weight of 1000 is added to the reaction vessel, and vacuum dehydrated at 80°C for 1 h. After cooling to 75°C, isophorone diisocyanate is added so that the molar ratio of isocyanate to diol is 2.0:1 (NCO:OH). The reaction is carried out at 75°C for 2 h to obtain polyurethane prepolymer.
[0084] (2) A 2-ureido-4[1H]-pyrimidinone derivative was added to the polyurethane prepolymer obtained in step (1) as a chain extender containing dynamic reversible hydrogen bond units. The amount added was 10% of the mass of the polyurethane prepolymer. After reacting at 65°C for 1 h, hydroxyethyl methacrylate was added as a capping monomer with a vinyl unsaturated structure. The amount added was 15% of the mass of the polyurethane prepolymer, and the reaction was continued for another 1 h. After the reaction was completed, deionized water was added and the mixture was dispersed to obtain a polyurethane dispersion containing polymerizable unsaturated groups.
[0085] (3) An acrylate monomer composition consisting of methyl methacrylate, butyl methacrylate, and hydroxyethyl methacrylate is added to the polyurethane dispersion obtained in step (2), along with a mixture of phosphate methacrylate and dopamine methacrylamide accounting for 80% of the total amount of interfacial anchoring monomers, and potassium persulfate initiator. In-situ emulsion polymerization is then carried out at 85°C for 3 hours to obtain a polyurethane-acrylate composite resin. In this scheme, based on solid mass conversion, the mass ratio of acrylate monomers to the polyurethane solid component in the polyurethane dispersion is 1.5:1; the amount of initiator added is 2.0% of the mass of the acrylate monomers. The obtained polyurethane-acrylate composite resin has an average particle size of approximately 300 nm, and the acrylate polymer component accounts for approximately 60% of the total mass of the composite resin.
[0086] (4) Multi-walled carbon nanotubes, the remaining 20% of the mixture of phosphate methacrylate and dopamine methacrylamide, and polycarboxylate dispersant were added to deionized water. The mixture was first sheared at 8000 rpm for 120 min, and then ultrasonically dispersed at 500 W for 10 min to obtain a multi-walled carbon nanotube dispersion. In this scheme, the diameter of the multi-walled carbon nanotubes was 5-20 nm, the length was 8-15 μm, and the specific surface area was about 300 m² / g; the mass ratio of multi-walled carbon nanotubes to dispersant was 1:0.8, and the solid content of the resulting dispersion was 20%.
[0087] (5) Mix the multi-walled carbon nanotube dispersion obtained in step (4) with the polyurethane-acrylate composite resin obtained in step (3), then add conductive carbon black and 2-amino-2-methyl-1-propanol, and stir until homogeneous to obtain a conductive slurry. Based on 100% of the total mass of the conductive slurry, excluding the aqueous medium, all components are calculated by effective solids or effective ingredients. The conductive slurry includes: Multi-walled carbon nanotubes 2.5%; Conductive carbon black 1.25%; Polyurethane-acrylate composite resin 8.25%; Interface anchoring unit 0.8%; Dispersant 2.0%; 0.15% of 2-amino-2-methyl-1-propanol; The remainder is deionized water.
[0088] The resulting conductive slurry had a pH of 9.2 and a solid content of 14.95%. Based on solid mass conversion, the mass ratio of multi-walled carbon nanotubes, polyurethane-acrylate composite resin, and conductive carbon black was 1:3.3:0.5. Example 6
[0089] In this embodiment, a carbon nanotube conductive paste with dynamic reversible hydrogen bond composite resin was prepared. The specific preparation process is as follows.
[0090] (1) Under the condition that the system is kept dry, polyether diol with a number average molecular weight of 5000 is added to the reaction vessel, and vacuum dehydrated at 80°C for 1 h. After cooling to 60°C, hexamethylene diisocyanate is added so that the molar ratio of isocyanate to diol is 1.2:1 (NCO:OH). The reaction is carried out at 60°C for 4 h to obtain polyurethane prepolymer.
[0091] (2) Bis(hydroxyethyl)urea was added to the polyurethane prepolymer obtained in step (1) as a chain extender containing dynamic reversible hydrogen bond units, and the amount added was 1% of the mass of the polyurethane prepolymer. After reacting at 50°C for 2 hours, hydroxypropyl acrylate was added as a capping monomer with a vinyl unsaturated structure, and the amount added was 5% of the mass of the polyurethane prepolymer. The reaction was then carried out for another hour. After the reaction was completed, deionized water was added and the mixture was dispersed to obtain a polyurethane dispersion containing polymerizable unsaturated groups.
[0092] (3) An acrylate monomer composition consisting of ethyl acrylate and methyl methacrylate is added to the polyurethane dispersion obtained in step (2), along with 20% of the total amount of interfacial anchoring monomers, including catechol acrylate and azobisisobutyramidine hydrochloride initiator. In-situ emulsion polymerization is then carried out at 70°C for 4 hours to obtain a polyurethane-acrylate composite resin. In this scheme, based on solid mass conversion, the mass ratio of acrylate monomers to the polyurethane solid component in the polyurethane dispersion is 0.3:1; the amount of initiator added is 0.1% of the mass of the acrylate monomers. The obtained polyurethane-acrylate composite resin has an average particle size of approximately 120 nm, and the acrylate polymer component accounts for approximately 23% of the total mass of the composite resin.
[0093] (4) Add multi-walled carbon nanotubes, the remaining 80% of catechol acrylate and polycarboxylate dispersant to deionized water, first shear at 4000 rpm for 60 min, then ultrasonically disperse at 200 W for 30 min to obtain a multi-walled carbon nanotube dispersion. In this scheme, the diameter of the multi-walled carbon nanotubes is 10-30 nm, the length is 5-10 μm, and the specific surface area is about 150 m² / g; the mass ratio of multi-walled carbon nanotubes to dispersant is 1:0.2, and the solid content of the obtained dispersion is 10%.
[0094] (5) Mix the multi-walled carbon nanotube dispersion obtained in step (4) with the polyurethane-acrylate composite resin obtained in step (3), then add conductive carbon black and ammonia solution, and stir until homogeneous to obtain a conductive slurry. Based on 100% of the total mass of the conductive slurry, where all components except the aqueous medium are based on the mass of effective solids or effective ingredients, the above conductive slurry includes: Multi-walled carbon nanotubes 2.0%; Conductive carbon black 0.6%; Polyurethane-acrylate composite resin 5.0%; Interface anchoring unit: 0.08%; Dispersant 0.4%; The ammonia solution contains 0.05% of the active ingredient. The remainder is deionized water.
[0095] The resulting conductive slurry had a pH of 7.8 and a solid content of 8.13%. Based on solid mass conversion, the mass ratio of multi-walled carbon nanotubes, polyurethane-acrylate composite resin, and conductive carbon black was 1:2.5:0.3. Comparative Example 1
[0096] This comparative example is used for comparison with Example 1. The addition ratio of each major component in this comparative example is basically the same as that in Example 1. The main difference is that this comparative example does not prepare polyurethane-acrylate composite resin, but uses ordinary polyurethane resin dispersion and acrylate resin dispersion as resin components after physical mixing. The types and effective component ratios of the remaining multi-walled carbon nanotubes, conductive carbon black, interface anchoring monomers, dispersants, pH adjusters and aqueous media are basically consistent with those in Example 1.
[0097] Specifically, a general polyurethane resin dispersion and a general acrylate resin dispersion were mixed at a solid mass ratio of 1:0.8 to obtain a physically blended resin dispersion. Subsequently, multi-walled carbon nanotubes, conductive carbon black, interface anchoring monomers, dispersants, pH adjusters, and deionized water were mixed and dispersed in the same effective component ratio as in Example 1 to obtain the conductive slurry of this comparative example.
[0098] Based on a total mass of 100% of the conductive paste in this comparative example, where, except for the aqueous medium, all components are measured by effective solids or effective ingredients, the conductive paste in this comparative example includes: Multi-walled carbon nanotubes 3.0%; Conductive carbon black 0.8%; Physically blended resins: 8.4%; Interface anchoring unit 0.6%; Dispersant 1.2%; Triethanolamine 0.2%; The remainder is deionized water.
[0099] The conductive paste obtained in this comparative example had a pH of 8.5 and a solid content of 14.2%. Therefore, the difference between this comparative example and Example 1 is that a polyurethane-acrylate composite resin structure was not formed. Comparative Example 2
[0100] This comparative example is used to compare with Example 1. The proportions of each component and the preparation steps in this comparative example are basically the same as those in Example 1. The main difference is that no chain extender containing a dynamic reversible hydrogen bond structure is introduced into the polyurethane chain segment. Instead, a common small molecule diol chain extender is used for chain extension.
[0101] Specifically, in the preparation of the polyurethane prepolymer, polycarbonate diol with a number average molecular weight of 2000 and isophorone diisocyanate were used, with a molar ratio of 1.6:1 (NCO:OH). The reaction conditions were the same as in Example 1. Ethylene glycol was then added as a common chain extender, and hydroxyethyl methacrylate was added for unsaturated end-capping. In-situ emulsion polymerization, carbon nanotube dispersion, and mixing and slurry preparation were then carried out. Except for the absence of a dynamically reversible hydrogen-bonded chain extender, the types and proportions of other components were the same as in Example 1.
[0102] Based on a total mass of 100% of the conductive paste in this comparative example, where, except for the aqueous medium, all components are measured by effective solids or effective ingredients, the conductive paste in this comparative example includes: Multi-walled carbon nanotubes 3.0%; Conductive carbon black 0.8%; Polyurethane-acrylate composite resin: 8.4%; Interface anchoring unit 0.6%; Dispersant 1.2%; Triethanolamine 0.2%; The remainder is deionized water.
[0103] The conductive paste obtained in this comparative example has a pH of 8.5 and a solid content of 14.2%. The difference between this comparative example and Example 1 is that the polyurethane segments do not contain dynamic reversible hydrogen bond structures. Comparative Example 3
[0104] This comparative example is used to compare with Example 1. The proportions of each component and the preparation steps in this comparative example are basically the same as those in Example 1. The main difference is that the interface anchoring monomer is not introduced in a stepwise manner, but is added all at once during the carbon nanotube dispersion stage.
[0105] Specifically, a polyurethane dispersion containing polymerizable unsaturated groups was prepared according to the method of Example 1; only acrylate monomers and ammonium persulfate initiator were added during the in-situ emulsion polymerization stage, without adding interface anchoring monomers; after the polyurethane-acrylate composite resin was formed, all dopamine methacrylamide was added to the aqueous system along with multi-walled carbon nanotubes and dispersant for high-speed shearing and ultrasonic dispersion, and then mixed with composite resin, conductive carbon black and pH adjuster to obtain a comparative conductive slurry.
[0106] Based on a total mass of 100% of the conductive paste in this comparative example, where, except for the aqueous medium, all components are measured by effective solids or effective ingredients, the conductive paste in this comparative example includes: Multi-walled carbon nanotubes 3.0%; Conductive carbon black 0.8%; Polyurethane-acrylate composite resin: 8.4%; Interface anchoring unit 0.6%; Dispersant 1.2%; Triethanolamine 0.2%; The remainder is deionized water.
[0107] The conductive slurry obtained in this comparative example has a pH of 8.5 and a solid content of 14.2%. The difference between this comparative example and Example 1 is that the interface anchoring monomer was not introduced in a stepwise manner, where part of it participates in the formation of the acrylate polymer component and the remainder is used for adsorption on the carbon nanotube surface. Application Example 1
[0108] The conductive pastes obtained in Examples 1-6 and Comparative Examples 1-3 were used to prepare lithium-ion battery samples, and the specific procedures are as follows: (1) Preparation of negative electrode slurry Using silicon-carbon 500 as the negative electrode active material, based on 100% of the total mass of the negative electrode solid components, 95.8% of silicon-carbon 500, 1.0% of sodium carboxymethyl cellulose, 2.0% of styrene-butadiene rubber, and one of Examples 1-6 and Comparative Examples 1-3 were weighed to prepare a conductive slurry. The equivalent solid component of the conductive slurry accounted for 1.2% of the total mass of the negative electrode solid components. Deionized water was added as a dispersion medium, and vacuum stirring and dispersion were performed to obtain the silicon-carbon negative electrode slurry. The solid content of the above silicon-carbon negative electrode slurry was controlled at 40% to 50%, and the viscosity was controlled at 3000 to 8000 mPa·s. The slurry was degassed under vacuum and then used for coating.
[0109] (2) Preparation of negative electrode sheet The silicon-carbon anode slurry obtained in step (1) is uniformly coated onto the surface of an 11-micron copper foil current collector. After pre-drying at 80–100°C, it is then vacuum-dried at 85°C to obtain the initial anode sheet. The obtained initial anode sheet is rolled to control the compaction density of the anode sheet at 1.45–1.70 g / cm³, and then die-cut to obtain the silicon-carbon anode sheet.
[0110] (3) Preparation of positive electrode sheet Using ternary 8-series cathode material as the cathode active material, based on a total mass of 100% of the cathode solid components, 96.0% of the ternary 8-series cathode material, 1.5% of the conductive carbon black, and 2.5% of the polyvinylidene fluoride were weighed out and dispersed by stirring with N-methylpyrrolidone as the solvent to obtain a cathode slurry. The obtained cathode slurry was coated onto the surface of a 16-micron aluminum foil current collector, and then dried, rolled, and die-cut to obtain a ternary 8-series cathode sheet.
[0111] (4) Preparation of 1Ah lithium-ion battery The silicon-carbon negative electrode obtained in step (2) is used as the negative electrode, and the ternary 8-series positive electrode obtained in step (3) is used as the positive electrode. A 16-micron PE base film is used as the separator, and the positive and negative electrode capacities are matched according to the designed capacity of 1Ah. The positive electrode, PE base film separator and negative electrode are assembled into a cell by stacking. Conventional lithium-ion battery electrolyte is injected, and after encapsulation, standing, formation and capacity testing, a lithium-ion battery with a rated capacity of 1Ah is obtained.
[0112] The electrolyte used is a carbonate electrolyte system containing LiPF6, and the N / P capacity ratio of the positive and negative electrodes is controlled at 1.08-1.12. The formation process can be carried out using a low-current pre-charge method, followed by degassing, secondary sealing, and capacity sorting.
[0113] Performance tests were conducted on the conductive pastes prepared in the above embodiments and comparative examples, as well as the batteries prepared in the application examples, as detailed below: (1) Storage stability test of conductive paste: The storage stability of conductive paste was evaluated by rotational viscometer and visual observation. After sealing the sample, it was placed in an environment of 25°C. The viscosity was tested at the initial stage, 1 month, 3 months and 6 months, and the presence of stratification, sedimentation, flocculation or obvious agglomeration was recorded. Before the test, the sample was stirred at low speed to make the paste state as uniform as possible. After standing to remove bubbles, the viscosity was measured.
[0114] (2) Particle size test of polyurethane-acrylate composite resin: The particle size of polyurethane-acrylate composite resin was tested using a dynamic light scattering particle size analyzer. Before the test, the composite resin dispersion was diluted with deionized water to a suitable concentration, stirred at low speed until uniform, and allowed to stand to remove bubbles before measuring the particle size distribution. The average value of three tests was recorded as the result.
[0115] (3) Stability test of negative electrode slurry: The stability of negative electrode slurry was evaluated by static observation and viscosity change. The silicon-carbon negative electrode slurries obtained in the application example were sealed and placed at 25°C. The slurry state was observed at 6h, 24h and 48h respectively. Phenomena such as sedimentation, stratification, thickening, water separation or thixotropic abnormalities were recorded to determine the compatibility between the conductive slurry and the silicon-carbon 500, sodium carboxymethyl cellulose and styrene-butadiene rubber system.
[0116] (4) Silicon-carbon negative electrode peel strength test: The peel strength of the electrode is tested by peeling at 180°. After the silicon-carbon negative electrode is cut into the specified size, the coated surface is fixed to the tape or clamp, and tested three times under a constant speed of 100 mm / min and a load of 0.05 N. The average peel force is taken as the basis for evaluating the interfacial adhesion performance.
[0117] (5) Resistance test of silicon-carbon anode sheet: The resistance of silicon-carbon anode sheet was measured using a four-probe resistance tester. To ensure the validity of the comparison, all samples were tested under the same compaction density and the same coating density to evaluate the construction effect of the multi-walled carbon nanotube and conductive carbon black composite conductive network.
[0118] (6) Electrode flexibility test: The electrode flexibility was evaluated by the round rod bending method. The silicon-carbon negative electrode was bent around a round rod with a diameter of 5 mm and 3 mm respectively, and the coating was observed to see if it cracked, powdered or peeled off; then, a round rod with a diameter of 5 mm was used to be bent repeatedly 20 times to compare the maintenance of the coating integrity of different electrodes.
[0119] (7) Rate Performance Test: The rate performance test of the battery was conducted at 25°C. Taking a 1Ah lithium-ion battery after formation and capacity grading as the object, the 0.33C discharge capacity was used as the baseline capacity. The discharge capacities at 0.33C, 1C, 2C and 3C were tested sequentially, and the capacity retention rate at each rate was calculated to evaluate the electron transport capability of the negative electrode conductive network under high-rate discharge conditions. The capacity retention rate was calculated by the following formula: Rate Capacity Retention Rate = Discharge Capacity at Corresponding Rate / 0.33C Discharge Capacity × 100%.
[0120] (8) Cyclic performance test: The cycle life test was also conducted at 25°C. The battery was charged with 0.5C constant current and constant voltage and discharged with 1C constant current, with the voltage range controlled between 2.5 and 4.2V. The discharge capacity after 800 cycles was recorded, and the capacity retention rate was calculated by the ratio of the discharge capacity at 800 cycles to the initial discharge capacity. This result was used to compare the effects of different conductive pastes on the cycle stability of the silicon-carbon anode and the conductivity network retention capability.
[0121] (9) Electrochemical impedance spectroscopy: Electrochemical impedance spectroscopy was performed after formation and capacity testing and after 800 cycles. Before testing, the battery was adjusted to 50% SOC and allowed to stand for 2 hours. Then, the test was performed in the frequency range of 500kHz to 0.03Hz, with a perturbation voltage of 5 to 10mV. The effect of different conductive pastes on the stability of the electrode interface can be determined by the change in interfacial impedance.
[0122] The results of the above tests are as follows: like Figures 1-9 Electron microscopy observations of the conductive pastes from Examples 1-6 and Comparative Examples 1-3 are presented respectively. Figure 1-6Microscopic images of the conductive pastes prepared in Examples 1-6 are shown. The images reveal that in each example, the multi-walled carbon nanotubes are relatively uniformly dispersed, with a continuous network structure, small bundle diameter, and no obvious large-size agglomerations. Polyurethane-acrylate composite resin particles are distributed on the surface of the carbon nanotubes and in the network gaps, which helps improve interfacial adhesion and the stability of the conductive network. Figure 7-9 Microscopic images of the conductive pastes prepared according to proportions 1-3 show varying degrees of bundle aggregation, local entanglement, and discontinuous network distribution. This indicates that without the use of composite resin, the lack of dynamic reversible hydrogen bonding structures, or the stepwise introduction of interface anchoring monomers, the dispersion state and interfacial bonding effect of the paste are all reduced. These morphological observation images reflect the dispersion and interface improvement effects of the conductive paste of this application.
[0123] Results of conductive paste storage stability test It can be seen that after 6 months of sealed storage at 25°C, the viscosity change rate of the conductive pastes in Examples 1-6 remained between 16.7% and 20.5%, and the samples remained black and uniform, without obvious stratification, hard sedimentation, or large particle agglomeration. Taking Example 1 as an example, its initial viscosity was 5520 mPa·s, and after 6 months it was 6570 mPa·s, with a change rate of 19.0%; the initial viscosity of the other examples was 5020-5360 mPa·s, and after 6 months it was 5880-6270 mPa·s, showing good long-term storage stability overall.
[0124] Compared to the examples, Comparative Examples 1-3 showed a more significant viscosity increase during storage, with a viscosity change rate of 60.6%-67.9% over 6 months, accompanied by varying degrees of flocculation, agglomeration, slight sedimentation, or stratification. This indicates that simple physical blending of resins, the lack of dynamic reversible hydrogen bond structures, or the failure to introduce interfacial anchoring monomers in a stepwise manner all weaken the long-term dispersion stability of the carbon nanotube aqueous conductive slurry.
[0125] Stability test results of conductive paste negative electrode paste The viscosity changes and appearance of the negative electrode slurries of Examples 1-6 and Comparative Examples 1-3 during the standing process at 25°C are shown. The initial viscosity of the example group was 4100-4470 mPa·s, which decreased to 4400-5350 mPa·s after 24 hours of standing, and 4660-5620 mPa·s after 48 hours. Although the viscosity increased with standing time, it remained uniform after 48 hours without stratification or hard sedimentation, indicating that the conductive slurry has good compatibility with silicon carbide 500, CMC, and SBR systems.
[0126] The initial viscosity of the negative electrode slurry in Comparative Examples 1–3 was 4540–4800 mPa·s. After standing for 24 h and 48 h, the viscosity increased significantly, reaching 8410–8970 mPa·s and 9460–10510 mPa·s, respectively. Slight thickening, thixotropic abnormalities, or local flocculation phenomena were observed. This indicates that the failure to adopt the composite resin structure, dynamic reversible hydrogen bonding, or stepwise introduction method of interface anchoring monomers in this application will lead to a significant decrease in the dispersion stability of carbon nanotubes and the processing stability of the negative electrode slurry.
[0127] Table 3. Peel strength and diaphragm resistance tests Example 1 28.2 22.8 2.24 1.89 Example 2 25.5 17.8 2.34 1.81 Example 3 27.2 19.2 2.35 1.88 Example 4 29.6 21.5 2.43 1.94 Example 5 30.7 20.0 2.19 1.90 Example 6 25.8 18.5 2.43 1.91 Comparative Example 1 23.3 13.8 2.60 2.05 Comparative Example 2 24.2 14.2 2.55 1.98 Comparative Example 3 23.7 13.9 2.65 2.00 As shown in Table 3, the peel strength of the negative electrode sheets in Examples 1 to 6 was 25.5 to 30.7 mN / mm before rolling and 17.8 to 22.8 mN / mm after rolling. The surface resistance was 2.19 to 2.43 mΩ before rolling and 1.81 to 1.94 mΩ after rolling, indicating that the electrode sheets prepared by the conductive paste of this application still maintain good adhesion and conductivity after rolling.
[0128] In contrast, the peel strength of the electrodes in Comparative Examples 1 to 3 after rolling was only 13.8 to 14.2 mN / mm, and the diaphragm resistance after rolling was 1.98 to 2.05 mΩ, which was significantly higher than that in the Example Group. This indicates that when the polyurethane-acrylate composite resin and interface anchoring monomer system of this application were not used, the interfacial bonding force of the electrode decreased, the continuity of the conductive network was poor, and it was easy to cause a decrease in the processing stability and cycle performance of the electrode.
[0129] Table 4. Electrode Flexibility Test Example 1 No cracks Slight indentation, no powder falling off Complete coating Example 2 No cracks No obvious cracks Complete coating Example 3 No cracks minor cracks Basically complete Example 4 No cracks No obvious cracks Complete coating Example 5 No cracks minor cracks No obvious shedding Example 6 No cracks minor cracks No obvious shedding Comparative Example 1 minor cracks Obvious cracks Localized powder loss Comparative Example 2 minor cracks Obvious cracks Localized cracking Comparative Example 3 minor cracks Obvious cracks Localized detachment As shown in Table 4, the negative electrode coatings of Examples 1-6 exhibited relatively stable flexibility and coating integrity after bending tests on 5mm and 3mm diameter round rods and repeated bending 20 times. Specifically, the 5mm diameter round rod showed no cracks or only slight cracks after bending, while the 3mm diameter round rod showed only slight indentations or slight cracks. After repeated bending, the coating of the 5mm diameter round rod remained intact or basically intact, with no significant peeling, demonstrating good adhesion and flexibility between the conductive paste, the silicon-carbon negative electrode material, and the bonding system.
[0130] Comparative Examples 1 to 3 showed slight or significant cracks under the same test conditions. After repeated bending, some areas showed powdering, local cracking or peeling, indicating that when the conductive paste system of this application was not used, the flexibility and adhesion of the negative electrode coating decreased significantly, and it was easily damaged during bending or cycling.
[0131] Table 5. Ratio Performance Test Data Example 1 1035 98.14 96.35 95.2 Example 2 1028 97.6 95.75 94.6 Example 3 1031 97.9 95.5 94.1 Example 4 1034 97.8 95.4 94.05 Example 5 1030 97.8 95.2 93.9 Example 6 1036 97.85 95.45 94.1 Comparative Example 1 1022 96 92 88.5 Comparative Example 2 1025 96.5 93 89.5 Comparative Example 3 1020 96.1 92.5 88.8 As shown in Table 5, the discharge capacity of batteries in Examples 1-6 at 0.33C is 1028-1036mAh, indicating that the capacity of each battery group is functioning normally. Regarding rate performance, the capacity retention rates of Examples 1-6 all reach over 97.6% under 1C conditions, 95.2%-96.35% under 2C conditions, and still maintain 93.9%-95.2% under 3C conditions, demonstrating relatively stable high-rate discharge capabilities.
[0132] In contrast, the capacity retention rates of Comparative Examples 1-3 were generally lower than those of the Example Group under 1C, 2C, and 3C conditions, especially under 3C conditions, where the retention rate was only 88.5%-89.5%. This indicates that the conductive paste of this application can improve the continuity of the conductive network of the silicon-carbon anode and reduce polarization during high-rate discharge, thereby improving rate performance.
[0133] From cycle capacity retention and interface impedance test data As can be seen, after 800 cycles, the capacity retention of Examples 1 to 6 still reached 94.2% to 95.8%, indicating that the silicon-carbon anode soft-pack battery using the conductive paste of this application has relatively stable long-cycle stability.
[0134] Regarding interface impedance, the initial interface impedance of Examples 1–6 was 13.4–14.2 mΩ, and after 800 cycles, the interface impedance was 16.3–18.4 mΩ, with an impedance growth rate of 21.6%–30.4%, which was controlled within a low range. Among them, Example 5 had the lowest impedance growth rate at 21.6%, corresponding to the highest capacitance retention rate of 95.8% after 800 cycles, indicating that it had superior interface stability and conductive network retention during cycling.
[0135] Although the initial capacities of Comparative Examples 1-3 were close to those of the Example Group, their 800-cycle capacity retention was only 82.6%-85.1%, significantly lower than that of the Example Group. Simultaneously, the interfacial impedance of Comparative Examples 1-3 increased to 23.1-23.9 mΩ after cycling, with an impedance growth rate of 50.0%-57.2%. This indicates that without the polyurethane-acrylate composite resin, dynamic reversible hydrogen bonding structure, or stepwise introduction method of interfacial anchoring monomers as described in this application, silicon-carbon anodes are more prone to interfacial impedance growth, conductive network decay, and decreased capacity retention during long-term cycling.
[0136] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom remain within the scope of this application.
Claims
1. A dynamic hydrogen-bonded composite resin carbon nanotube conductive paste, characterized in that, Based on 100% of the total mass of the conductive paste, the conductive paste consists of the following components by mass percentage: Multi-walled carbon nanotubes: 1.0%–6.0%; Conductive carbon black 0.1%–3.0%; Polyurethane-acrylate composite resin 5.0%~20.0%; Interface anchoring monomers: 0.05%–3.0%; Dispersant 0.1%–5.0%; pH adjuster 0.01%~1.0%; Water-based media balance; The polyurethane-acrylate composite resin is formed by chemical bonding of polyurethane segments and acrylate polymer components, and the polyurethane segments contain dynamic reversible hydrogen bond structures. The interface anchoring monomer has carbon nanotube adsorption groups and / or negative electrode material interface anchoring groups, and carries polymerizable reactive groups. The interface anchoring monomer is introduced in two parts in a stepwise manner, wherein the first part of the interface anchoring monomer is covalently bonded to the acrylate polymer component, and the second part of the interface anchoring monomer is adsorbed on the surface of the multi-walled carbon nanotubes.
2. The dynamic hydrogen-bonded composite resin carbon nanotube conductive paste according to claim 1, characterized in that, The dynamic reversible hydrogen bond structure is selected from one or more of the following: urea hydrogen bond structure, diurea hydrogen bond structure, and 2-urea-4[1H]-pyrimidinone (UPy) quadruple hydrogen bond structure.
3. The dynamic hydrogen-bonded composite resin carbon nanotube conductive paste according to claim 1, characterized in that, The interface anchoring monomer is selected from one or more of pyrene methacrylate, catechol acrylate, dopamine methacrylamide, and phosphate methacrylate.
4. The dynamic hydrogen-bonded composite resin carbon nanotube conductive paste according to claim 1, characterized in that, The multi-walled carbon nanotubes have a diameter of 5–30 nm, a length of 5–15 μm, and a specific surface area of 100–350 m² / g; the polyurethane-acrylate composite resin has an average particle size of 50–500 nm, wherein the acrylate polymer component accounts for 20%–70% of the total mass of the composite resin.
5. The dynamic hydrogen-bonded composite resin carbon nanotube conductive paste according to claim 1, characterized in that, The dispersant is selected from one or more of polyurethane dispersants, polycarboxylate dispersants, and lignin sulfonate dispersants; the pH adjuster is selected from one or more of triethanolamine, ammonia, and 2-amino-2-methyl-1-propanol; the conductive slurry has a pH of 7.5 to 10 and a solid content of 6% to 15%.
6. The dynamic hydrogen-bonded composite resin carbon nanotube conductive paste according to claim 1, characterized in that, Based on solid mass conversion, the mass ratio of the multi-walled carbon nanotubes, polyurethane-acrylate composite resin, and conductive carbon black is 1:2.0~3.3:0.1~0.
5.
7. A method for preparing a dynamic hydrogen-bonded composite resin carbon nanotube conductive paste according to any one of claims 1 to 6, characterized in that, Includes the following steps: (1) React polyether diol, polycarbonate diol or polyester diol with diisocyanate at 60-80°C for 2-4 hours to form polyurethane prepolymer; (2) Add a chain extender containing a dynamic reversible hydrogen bond structure to the polyurethane prepolymer and add a capping monomer containing vinyl unsaturated groups. React at 50-70°C for 1-2 hours, and then add an aqueous medium for dispersion to obtain a polyurethane dispersion containing polymerizable unsaturated groups. (3) Add acrylate monomer, first part of interface anchoring monomer and free radical initiator to the polyurethane dispersion, and carry out in-situ emulsion polymerization at 70-90°C to form polyurethane-acrylate composite resin. (4) The multi-walled carbon nanotubes, the second part of the interface anchoring monomer and the dispersant are dispersed to obtain a multi-walled carbon nanotube dispersion. (5) Mix the multi-walled carbon nanotube dispersion obtained in step (4) with the polyurethane-acrylate composite resin obtained in step (3), then add conductive carbon black and pH adjuster, and mix evenly to obtain conductive slurry.
8. The method for preparing dynamic hydrogen-bonded composite resin carbon nanotubes according to claim 7, characterized in that, In step (1), the number average molecular weight of the polyether diol, polycarbonate diol, or polyester diol is 500 to 5000, the diisocyanate is selected from one or more of isophorone diisocyanate, hexamethylene diisocyanate, and toluene diisocyanate, and the molar ratio of the diisocyanate to the diol is 1.2 to 2.0:1, calculated as NCO:OH.
9. The method for preparing dynamic hydrogen-bonded composite resin carbon nanotubes according to claim 7, characterized in that, In step (2), the amount of the chain extender containing the dynamic reversible hydrogen bond structure added is 1% to 10% of the mass of the polyurethane prepolymer; the end-capping monomer containing vinyl unsaturated groups is selected from one or more of hydroxyethyl methacrylate and hydroxypropyl acrylate, and the amount added is 5% to 15% of the mass of the polyurethane prepolymer.
10. The method for preparing dynamic hydrogen-bonded composite resin carbon nanotubes according to claim 9, characterized in that, In step (3), the acrylate monomer is selected from one or more of butyl acrylate, ethyl acrylate, methyl methacrylate, butyl methacrylate, hydroxyethyl acrylate, and hydroxyethyl methacrylate; the mass ratio of the acrylate monomer to the polyurethane solid component in the polyurethane dispersion is 0.3 to 1.5:1 based on solid mass; the amount of the free radical initiator added is 0.1% to 2.0% of the mass of the acrylate monomer; the first part of the interface anchoring monomer accounts for 20% to 80% of the total amount of interface anchoring monomer.
11. The method for preparing dynamic hydrogen-bonded composite resin carbon nanotubes according to claim 7, characterized in that, In step (4), the dispersion treatment is to first shear at high speed of 4000-8000 rpm for 60-120 min, and then disperse ultrasonically at 200-500W for 10-30 min; the mass ratio of the multi-walled carbon nanotubes to the dispersant is 1:0.2-0.8, and the solid content of the dispersion liquid is 10%-20%.
12. The method for preparing dynamic hydrogen-bonded composite resin carbon nanotubes according to claim 7, characterized in that, In step (5), the mass ratio of the multi-walled carbon nanotubes, polyurethane-acrylate composite resin and conductive carbon black is 1:2.0~3.3:0.1~0.5 based on solid mass conversion.
13. The application of the conductive paste according to any one of claims 1 to 6 or the conductive paste prepared by the preparation method according to any one of claims 7 to 12 in the preparation of the negative electrode sheet of a lithium-ion battery.